TIGR matrix for implant-based breast reconstruction – a long-term resorbable mesh. (2nd September 2018) - Cuffolo, Giulio; Holford, Nicholas C; Contractor, Kaiyumars; Tenovici, Alexandra
ABSTRACT: The use of biological and synthetic meshes to aid implant coverage in implant-based breast reconstruction is well established. This technique allows single stage implant-based reconstruction compared to the traditional technique which required tissue expansion before permanent implant placement and therefore involved two operations for the patient. They can further be used for pre-pectoral implant reconstructions in a similar direct-to-implant strategy. This retrospective observational study by Pompei et al has evaluated the use of TIGR Matrix, a long-term resorbable mesh, in 49 patients with 60 operated breasts for both reconstructive and aesthetic cases. They have reported their operative method and followed up their cases for a mean of 12 months. They have reported a cumulative mesh complication rate of 5.4% and one implant was explanted due to infection. They identified a significant correlation between obesity and mesh-related complications. This study is significant as there remains little data regarding the long term outcomes of resorbable synthetic mesh for breast reconstruction. Their reported complication rates are consistent with those in other studies for synthetic meshes. As synthetic meshes can be significantly cheaper than their biological counterparts, this work could promote more widespread use.